ENTREPRENEURIAL ORIENTATION OF LOCAL HANDICRAFTS PRODUCERS IN MANADO - Simbala, Nifia G.; Massie, James D. D.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2019)
Abstract: Entrepreneurial orientation plays an important role in development and improving business. Most of the SMEs in Manado, they have a strong enough the entrepreneurial orientation in their own business especially in handicrafts business sector. The purpose of this study was to analyze the importance of three main entrepreneurial orientationâ€™s indicators (innovativeness, proactiveness, risk-taking) in handicrafts business sector and how to see the opportunities that caused by Entrepreneurial orientation on local handicrafts producers in Manado. This study uses an exploratory approach with in-depth interview to collecting all the data from ten informants. The qualitative approach used in this study illustrates the importance of Entrepreneurial orientation for Local handicrafts producers in Manado. The result of this research shows that entrepreneurial orientation are closely related with handicrafts businesses especially for local handicrafts producers because the indicators from entrepreneurial orientationare really needs to be applied in business development to support businesses get more profit. Based on the findings, the recommendations of this study are for craftman in Manado, especially local handicrafts producers, North Sulawesi government and next researcher to develop and maintain these 3 indicators to become successful handicrafts producers, become a responsible government, and the next researcher should expanding the research area.Â Keywords: handicrafts, entrepreneurial orientation, inovativeness, proactiveness, risk-taking.